One-step microfluidic synthesis of Janus microhydrogels with anisotropic thermo-responsive behavior and organophilic/hydrophilic loading capability - Seo, Kyoung Duck (Langmuir : the ACS journal of surfaces and colloids, 2013)
We report one-step microfluidic synthesis and characterization of novel Janus microhydrogels composed entirely of the same base material, N-isopropylacrylamide (NIPAAm). The microhydrogels were fabricated by the microfluidic generation of Janus monomer microdroplets based on separation of a supersaturated aqueous NIPAAm solution into NIPAAm-rich and -poor phases followed by UV irradiation. The resulting Janus microhydrogels exhibited tunable anisotropic thermo-responsive behavior and organophilic/hydrophilic loading capability